Paper No S2.1: Cathodoluminescence Images and Spectra of Single Nanometer Sized Phosphor Crystals Excited in a Field Emission Transmission Electron Microscope (Invited Paper). Issue 1 (September 2015) - Silver, J.; den Engelsen, D.; Fern, G. R.; Harris, P.; Lipman, A.; Ireland, T. G.
Abstract In this article, cathodoluminescent images and spectra of a range of single nanometer‐sized phosphor crystals and quantum dots are presented to illustrate the power and potential of the technique as an aid to both characterize phosphor materials and assess their homogeneity.